HUBUNGAN ANTARA TRUST DENGAN SELF DISCLOSURE PADA REMAJA PUTRI PENGGUNA TIKTOK: RELATIONS BETWEEN TRUST AND SELF DISCLOSURE IN TIKTOK USERS OF TEENAGE GIRLS - Pradana Yitami Boer; Mario Pratama (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2022)
ABSTRACTIntroduction There is an increase in the use of social media, one of which is TikTok social media which is dominated by teenagers, especially young women. The aim of this research is to find out the relationship between trust and self disclosure in young women using TikTok in Padang City. Methods In this study using quantitative methods with a population of young women who are domiciled in the city of Padang. The sample in this study was 209 respondents and used purposive sampling technique. The measuring instrument uses a trust scale and a self disclosure scale. Results Based on the results of the analysis using product moment analysis, the correlation coefficient (R) = 0.595 with a significant value of p = 0.000 (p <0.05) means that there is a positive relationship between trust and self-disclosure in young women using TikTok in Padang City. Conclusions Thus, it shows that the higher the trust, the higher the level of self-disclosure among young women using TikTok in Padang City. Keywords: trust, self disclosure, adolescent women using TikTok ABSTRAK Pendahuluan Terjadinya peningkatan penggunaan media sosial, salah satunya media sosial TikTok yang didominasi oleh remaja khususnya remaja putri. Penelitian yang dilakukan memiliki tujuan untuk mengetahui adanya hubungan antara trust dengan self disclosure pada remaja putri pengguna TikTok di Kota Padang. Metode Pada penelitian ini menggunakan metode kuantitatif dengan populasi remaja putri yang domisili di Kota Padang. Sampel pada penelitian ini adalah 209 responden dan menggunakan teknik purposive sampling. Alat ukur menggunakan skala trust dan skala self disclosure. Hasil Berdasarkan hasil analisis menggunakan analisis product moment didapatkan koefisien yang korelasi (R) = 0.595 dengan nilai signifikan sebesar p= 0,000 (p< 0,05) artinya terdapat hubungan yang positif antara trust dengan self disclosure pada remaja putri pengguna TikTok di Kota Padang. Kesimpulan Penelitian ini menunjukkan bahwa semakin tinggi trust maka akan semakin tinggi tingkat self disclosure pada remaja putri pengguna TikTok di Kota Padang. Kata kunci: trust, self disclosure, remaja putri pengguna TikTok